Identification and characterisation of toxin-antitoxin systems in Helicobacter pylori tfs ICEs - Boampong, Kwadwo (2019)
The tfs gene clusters that largely comprise the main plasticity regions of H. pylori encode Type IV secretion systems (T4SS); Tfs3 T4SS and Tfs4 T4SS. Both tfs3 and tfs4 have been described as integrative and conjugative elements (ICEs) that can excise from a host chromosome and transfer to a recipient chromosome, thereby contributing to genetic variation of H. pylori population. Although many tfs-encoded genes are uncharacterised, the tfs3-encoded gene ctkA has been associated with induction of pro-inflammatory cytokines such as IL-8 and TNF-α, thereby increasing disease risk. The tfs4-encoded gene dupA is also a disease marker for duodenal ulcer disease.